РИТОРИЧНІ ЗАСОБИ І ПРИЙОМИ ЗАПОБІГАННЯ КОМУНІКАТИВНИМ ДЕВІАЦІЯМ - Переломова, О. С. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті розглядається проблема девіацій у комунікативному процесі в широкому розумінні комунікації в усіх її виявах, аналізуються причини їх виникнення, а також йдеться про можливості риторичних засобів і прийомів усунення перешкод на шляху досягнення комунікативної мети в різних прагматичних ситуаціях. Переломова Е.С. Риторические средства и приёмы упреждения коммуникативных девиаций. В статье рассматривается проблема девиаций в коммуникативном процессе в широком понимании коммуникации во всех её проявлениях, анализируются причины их возникновения, а также речь идет о возможностях риторических средств и приёмов устранения преград на пути к достижению коммуникативной цели в различных прагматических ситуациях. Ключевые слова: коммуникативные девиации, риторические средства и приёмы, коммуникативный акт, прагматичная ситуация, коммуникативная тактика, общение, коммуникат. Perelomova O.S. Rhetorical tools and techniques of prevention of communicative deviations. The article deals with the problem of deviations in the communicative process in the broad sense of communication in all aspects, analyzes their causes and possible rhetorical question about the means and methods of overcoming obstacles to achieve communicative goals in different pragmatic situations. Keywords: communicative deviation, rhetorical tools and techniques, communicative act, pragmatic situation, communication tactics, communication, communiqué.